Influence of annealing duration on structural, optical and electrical properties of AZO thin films grown on corning glass by dc magnetron sputtering. (June 2020) - Sugianto, S; Astuti, B; Marwoto, P; Firmahaya, N A; Aryanto, D; Isnaeni,
Abstract: Al doped ZnO (AZO) thin films were deposited using dc magnetron sputtering on corning glass substrate has successfully done. After deposition, the samples were annealed in vacuum ambient at temperature of 300 °C with variation in annealing duration of 0, 30, and 50 minutes, respectively. The structural, optical and electrical properties of these films have been investigated as a function of annealing duration. Thin films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), UV-Vis spectrometer and I-V measurements. AZO thin films without annealing treatment was showed amorphous structure. However, after annealed at 30 and 50 minutes, the films obtained were polycrystalline with a hexagonal wurtzite structure and preferred orientation in the (002) plane. Average optical transmittance of the AZO thin films was over 85%. In Addition, the electrical resistivity is reduced from 1.85 × 10 6 Ωcm to 1.93 × 10 2 Ωcm when applying annealing treatment. It's can be concluded, the annealing treatment in vacuum ambient was improved the crystallinity and simultaneously improved optical and electrical properties of AZO films.